A New Perspective on the Ruling Regarding The Sale of Dead Animals dnd Slaughterhouse By-Products - Abd Ulrahman Raad Nouri (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2025)
The mass death of animals for any reason is known as dead animals, and this mass death is considered a significant economic loss. Should they be thrown in the streets and become a cause for spreading diseases? Or should they be thrown into the water to cause another disaster for aquatic animals? Of course not, the damage remains the same. In fact, recycling these animals and deriving useful products from them contributes to environmental preservation on one hand and economic development on the other. And the carcasses of dead animals and slaughterhouse remains can be utilized in many ways after being processed in appropriate methods. God Almighty said: (And the cattle He created for you, in them is warmth and [numerous] benefits). The Bee [5]. The Hanafi scholar, Al-Din Al-Babarti, may Allah have mercy on him, said: "There is no harm in selling the bones, tendons, wool, horns, hair, and hides of a dead animal and benefiting from all of them; because they are pure and not rendered impure by death due to the absence of life.